Analysis of mutations in GBA gene in Ukrainian patients with Gaucher disease - Olkhovych, N.V.; Nedoboy, A.M.; Pichkur, N.O.; Gorovenko, N.H. (Вiopolymers and Cell, 2017)
Gaucher disease (MIM 230800) is the most common storage disorder, caused by hereditary deficiency of the lysosomal enzyme of glucocerebrosidase (EC 3.2.1.45). Human glucocerebrosidase gene (GBA) is mapped to the 1q21 locus, it is 7.5 kb long and consists of 11 exons. According to human gene mutation databases, there are over 300 currently described pathogenic GBA variants, most of them are related to the development of Gaucher disease. Aim. To identify rearrangements in the GBA gene which conditioned the development of Gaucher disease in Ukrainian patients, to compare their spectrum with the variants in patients from Slavonic and other European countries and to evaluate genotype-phenotype associations for this disease. Methods. The Sanger’s method of direct automated sequencing using ABI 3130 analyzer (Applied Biosystems). Results. We identified 96.8 % of mutant alleles in Ukrainian patients with Gaucher disease. Six new and previously not described rearrangements of the GBA gene were identified. Conclusion. The comparison of genotypes with the linical form of the disease demonstrated that our results agree with the currently recognized genotype-phenotype correlations, which allow predicting the type and clinical course of the Gaucher disease to some degree.